Children and Generative Artificial Intelligence (GenAI) in Australia: The Big Challenges - Leaver, Tama; Srdarov, Suzanne (ARC Centre of Excellence for the Digital Child, 2025)
GenAI tools are great at reproducing what probabilistically comes next, but these models produce all kinds of errors because there is no understanding, no intelligence. It is vital that these tools are used carefully and critically.